KORELASIÃÂ ANTARAÃÂ KEAKTIFANÃÂ DALAMÃÂ ORGANISASIÃÂ KEMAHASISWAANÃÂ ÃÂ DENGANÃÂ PRESTASIÃÂ BELAJARÃÂ MAHASISWAÃÂ ÃÂ - Aziz, Abdul; Sunyoto, -; Widodo, Rahmad Doni (Jurnal Pendidikan Teknik Mesin, 2008)
TujuanÃÂ penelitianÃÂ iniÃÂ adalahÃÂ untukÃÂ mengetahuiÃÂ keaktifanÃÂ mahasiswaÃÂ dalamÃÂ organisasiÃÂ kemahasiswaan,ÃÂ mengetahuiÃÂ  korelasiÃÂ  antaraÃÂ  keaktifanÃÂ  dalamÃÂ  organisasiÃÂ  kemahasiswaanÃÂ  denganÃÂ  prestasiÃÂ  belajarÃÂ mahasiswa.ÃÂ PopulasiÃÂ dalamÃÂ penelitianÃÂ iniÃÂ adalahÃÂ mahasiswaÃÂ ProgramÃÂ StudiÃÂ PendidikanÃÂ TeknikÃÂ Mesin,ÃÂ  JurusanÃÂ TeknikÃÂ Mesin,ÃÂ FakultasÃÂ  TeknikÃÂ  UniversitasÃÂ  NegeriÃÂ  SemarangÃÂ  angkatanÃÂ  2005,ÃÂ  2006,ÃÂ  danÃÂ  2007.ÃÂ  SampelÃÂ  penelitianÃÂ  sebanyakÃÂ  81ÃÂ mahasiswa.ÃÂ  DataÃÂ  dianalisisÃÂ  menggunakanÃÂ  korelasiÃÂ  sederhana.ÃÂ  HasilÃÂ  penelitianÃÂ  menunjukkanÃÂ  bahwaÃÂ  keaktifanÃÂ mahasiswaÃÂ  dalamÃÂ  organisasiÃÂ  kemahasiswaanÃÂ  tergolongÃÂ  sedang.ÃÂ  HasilÃÂ  penelitianÃÂ  iniÃÂ  jugaÃÂ menunjukkanÃÂ adanyaÃÂ hubunganÃÂ yangÃÂ positifÃÂ antaraÃÂ keaktifanÃÂ dalamÃÂ organisasiÃÂ kemahasiswaanÃÂ denganÃÂ prestasiÃÂ belajarÃÂ mahasiswa.ÃÂ DariÃÂ penelitianÃÂ  iniÃÂ  disarankanÃÂ  agarÃÂ mahasiswaÃÂ  lebihÃÂ dapatÃÂ memanfaatkanÃÂ organisasiÃÂ  kemahasiswaanÃÂ  sebagaiÃÂ  saranaÃÂ pengembanganÃÂ diri. KataÃÂ kunciÃÂ :ÃÂ keaktifan,ÃÂ organisasiÃÂ kemahasiswaan,ÃÂ prestasiÃÂ belajar.ÃÂ TheÃÂ objectivesÃÂ ofÃÂ thisÃÂ researchÃÂ areÃÂ toÃÂ identifyÃÂ theÃÂ activenessÃÂ ofÃÂ studentsÃÂ inÃÂ studentÃÂ affairsÃÂ organization,ÃÂ toÃÂ findÃÂ outÃÂ theÃÂ correlationÃÂ betweenÃÂ theÃÂ activenessÃÂ ofÃÂ studentsÃÂ inÃÂ theÃÂ organizationÃÂ andÃÂ theirÃÂ achievementÃÂ ofÃÂ studyÃÂ inÃÂ academicÃÂ life.ÃÂ PopulationÃÂ ofÃÂ theÃÂ researchÃÂ wasÃÂ theÃÂ studentsÃÂ ofÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ program,ÃÂ MechanicalÃÂ  EngineeringÃÂ  department,ÃÂ  FacultyÃÂ  ofÃÂ  Engineering,ÃÂ  SemarangÃÂ  StateÃÂ UniversityÃÂ  yearÃÂ  2005,ÃÂ  2006,ÃÂ  andÃÂ 2007.ÃÂ TheÃÂ sampleÃÂ ofÃÂ theÃÂ researchÃÂ wasÃÂ 81ÃÂ students.ÃÂ TheÃÂ dataÃÂ wasÃÂ analyzedÃÂ usingÃÂ simpleÃÂ correlation.ÃÂ TheÃÂ resultÃÂ ofÃÂ itÃÂ showsÃÂ thatÃÂ theÃÂ levelÃÂ ofÃÂ studentÃÂ activenessÃÂ inÃÂ studentÃÂ affairsÃÂ organizationÃÂ isÃÂ medium.ÃÂ ItÃÂ alsoÃÂ showsÃÂ thatÃÂ thereÃÂ isÃÂ positiveÃÂ correlationÃÂ betweenÃÂ theÃÂ activenessÃÂ ofÃÂ studentsÃÂ inÃÂ studentÃÂ affairsÃÂ organizationÃÂ andÃÂ theirÃÂ achievementÃÂ inÃÂ study.ÃÂ ItÃÂ isÃÂ sugÃ¢â¬ÂgestedÃÂ toÃÂ studentsÃÂ forÃÂ usingÃÂ studentÃÂ affairsÃÂ organizationÃÂ asÃÂ aÃÂ selfÃ¢â¬ÂdevelopmentÃÂ medium. ÃÂ  Keywords:ÃÂ activeness,ÃÂ studentÃÂ affairsÃÂ organization,ÃÂ theÃÂ achievementÃÂ ofÃÂ study ÃÂ